1987
DOI: 10.1182/blood.v69.2.640.640
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant tumor necrosis factor causes activation of human granulocytes

Abstract: We have tested the hypothesis that tumor necrosis factor (TNF), by binding to and activating granulocytes, may contribute to the pathogenesis of gram-negative sepsis and the adult respiratory distress syndrome (ARDS). Buffy coat granulocytes incubated with as little as 0.5 ng/mL of recombinant TNF (rTNF) showed a dose-related increase in nitroblue tetrazolium dye reduction, in granulocyte polarization, in superoxide anion release, and in visually apparent aggregation. Purified lipopolysaccharide (1 microgram/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

1988
1988
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(29 citation statements)
references
References 22 publications
1
26
2
Order By: Relevance
“…When patients admitted because of sepsis or septic shock present elevated serum TNF-a levels (> 50 pg mL -1 ) at presentation, they have a better survival rate than those with low TNF-a levels [16]. It has been demonstrated that TNF-a is beneficial to the host because it will augment neutrophil functions, and these activated neutrophils will clear invading organisms more effectively [17]. In contrast, other studies did not correlate the presence of circulating TNF-a with the patients' outcome [18][19][20][21][22].…”
Section: Cytokines and Acute-phase Proteins In Pneumonia 313mentioning
confidence: 99%
“…When patients admitted because of sepsis or septic shock present elevated serum TNF-a levels (> 50 pg mL -1 ) at presentation, they have a better survival rate than those with low TNF-a levels [16]. It has been demonstrated that TNF-a is beneficial to the host because it will augment neutrophil functions, and these activated neutrophils will clear invading organisms more effectively [17]. In contrast, other studies did not correlate the presence of circulating TNF-a with the patients' outcome [18][19][20][21][22].…”
Section: Cytokines and Acute-phase Proteins In Pneumonia 313mentioning
confidence: 99%
“…MD). To cxelude the influence of endotoxin, polymyxin B (Sigma) al a concentration of 5 /ig/ml was added to the cultures at the beginning of the culture period [12]. The supernatants were collected and the concentrations of lL-6.…”
Section: Measurement Of Cytokines By Elisamentioning
confidence: 99%
“…Infusion of endotoxin elicits lymphopenia and a transient granulocytopenia followed by granulocytosis. While several investigators have tried to clarify the disappearance of granulocytes from peripheral blood during the granuloeytopenia [4,5] little is known about the fate ofthe lymphocytes during the lymphopenia: are the lymphocytes redistributed to other tissues, accumulating in the lungs or destroyed in the reticuloendothelial system ofthe liver?…”
Section: Introductionmentioning
confidence: 99%